805 Safety and emerging evidence of immune modulation of the live biotherapeutic MRx0518 in the neoadjuvant setting for patients awaiting surgical removal of solid tumours. (10th December 2020) - Lythgoe, Mark; Stebbing, Justin; Pickford, Emily; Glasmacher, Axel; Adriani, Marsilio; Fyvie, Gayle; Frampton, Adam; Stevenson, Alex; Krell, Jonathan
Abstract : Background: The gut microbiome has emerged as a promising innovative therapeutic target for immune-stimulation treatment of solid tumours. MRx0518 is a novel, gut microbiome-derived oral live biotherapeutic. It has potent anti-tumorigenic efficacy in the preclinical setting including murine models of lung (LLC1), kidney (Renca) and breast (EMT6) cancer. 1 In these models, a significant reduction in tumour growth has been demonstrated, including induction of immunostimulatory responses with tumour infiltration of NK cells, CD8+ and CD4+ T-cells. MRx0518 is under investigation in various oncological settings, including in combination with immune checkpoint inhibitors (NCT03637803 ) and radiotherapy (NCT04193904 ). Methods: Treatment naïve patients were recruited from April 2019 to February 2020. Patients were eligible if they received a histologically confirmed diagnosis of cancer (solid tumours) scheduled for surgical resection. Patients received 1 capsule of MRx0518 (1x1010 to 1x1011 CFU) twice daily from inclusion until the day preceding surgery (maximum 28 days therapy). The primary study outcome is to evaluate safety and tolerability of MRx0518 monotherapy in treatment naïve patients. Additional exploratory outcomes including identifying surrogate biomarkers of efficacy, microbiome analysis, effect on metabonomic markers and identification of histological and genomic alterations in paired pre-treatment (diagnostic biopsy) and post-treatment (surgical specimen) samples. Results: In part A, 17 patients received treatment, across tumour groups including breast (n=8), prostate (n=4), uterine (n=3), melanoma (n=1) and bladder (n=1). MRx0518 was well tolerated by all, with no grade 3/4 CTCAE toxicity reported, no severe adverse effects or treatment discontinuations. All patients proceeded to surgery, however the COVID-19 pandemic delayed surgery in 3 cases. Analysis of the first 5* patient paired samples utilising the NanoString Pan Cancer IO 360TM Gene Expression panel has demonstrated significant changes in gene expression profiles in 48 genes (p Conclusions: This study has demonstrated the safety and tolerability of the live biotherapeutic MRx0518 in treatment naïve cancer patients. Exploratory analyses of post-treatment samples has echoed preclinical observations of increased infiltration of immune cells following treatment and will undergo further validation. Part B will focus on investigating efficacy in a further 100 treatment naïve patients with a placebo-controlled arm. Trial Registration: NCT03934827 Ethics Approval: The study was approved by East of England - Cambridge East Research Ethics Committee approval number 18/EE/0091 Reference: Lauté-Caly DL, Raftis EJ, Cowie P, et al. The flagellin of candidate live biotherapeutic Enterococcus gallinarum MRx0518 is a potent immunostimulant. Scientific Reports 2019;9(1):1-14. doi:10.1038/s41598-018-36926-8 *Data analysis has been censored at 18/9/2020, further samples analysis is ongoing and will be updated.